Goosebumps : My Hairiest Adventure - Book 26 (New York : Scholastic Inc., 1994)
After rubbing on some old INSTA-TAN, Larry Boyd notices dark spikey hair growing on his hands and face.
"An Apple paperback."
Keywords: Horror fiction; Fantasy fiction